The Acta Pekinensia or Historical Records of the Maillard de Tournon Legation - SJ, Kilian Stumpf (Asian Studies E-Books Online, Collection 2024., 2024)
The Acta Pekinensia is a Latin manuscript found in the Jesuit Roman Archives. It is a record of the papal legation to China of Charles Maillard de Tournon, from his arrival in China to his death in Macau. It was compiled by Kilian Stumpf, a German Jesuit missionary/scientist serving at the court of the Kangxi emperor of China. Stumpf was in a privileged position to record day by day the events of this crucial episode not only in the history of Christianity in China but in Chinese-Western relations. This annotated translation provides a full documentation and an acute and lively commentary on the clash of values which resulted in the failure of the legation and the condemnation of Chinese Rites.